Optimal portfolio management and its impact on market value: an analytical study in the Dubai Financial Market for the period (2013-2022) - Alaa Ali Saleh Judeh *; Assistant teacher Ghassan Ali Abdul Hassan Majour (مجلة الدراسات الاقتصادية والادارية)
This study aims to identify the effectiveness of optimal management of investment portfolios and the extent of its impact on the market value of companies and financial institutions, to demonstrate the extent of the role of optimal management of investment portfolios, as well as to demonstrate the impact of diversification of assets and investment instruments on both returns and financial risks. The study was conducted on companies operating in the Dubai Financial Market (DFM) for the period (2013-2022). The cut-off model was used to identify the companies included in the portfolio. The study came in four axes. The first section included the theoretical dimension of the investment portfolio, while the second section dealt with the theoretical dimension of the market value, while the third section dealt with the practical aspect of the study and the fourth section dealt with conclusions and recommendations. The study reached a number of conclusions, including that there are (9) companies nominated for the optimal investment portfolio for the Iraq Stock Exchange out of (44) companies listed on the Iraq Stock Exchange, i.e. (20%) of the total companies, as well as the existence of a statistically significant relationship between the returns and the market value of the companies included in the optimal investment portfolio. The study recommended the necessity of Providing a safe investment environment that enhances the efficiency of the financial market, which would raise the efficiency of companies operating in the market and thus increase the number of companies included in the components of the optimal investment portfolio, which leads to increased diversification of the assets of the investment portfolio.